2022
DOI: 10.1101/2022.11.15.513554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Peroxiredoxin-P38 MAPK scaffold increases MAPK activity by MAP3K-independent mechanisms

Abstract: Peroxiredoxins (Prdx) utilize reversibly oxidized cysteine residues to reduce peroxides but also to promote H2O2 signal transduction, including H2O2-induced activation of P38 MAPK. Prdx form H2O2-induced disulfide complexes with many proteins, including multiple kinases involved in P38 MAPK signaling. Here we show that a genetically-encoded fusion between Prdx and the P38 MAPK is sufficient to hyperactivate the kinase in yeast and human cells by a mechanism that does not require the H2O2-sensing cysteine of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 70 publications
(179 reference statements)
0
3
0
Order By: Relevance
“…This is consistent with work in other organisms showing that protein tyrosine kinases are susceptible to oxidative-stress mediated inhibition through oxidation of the active site cysteine residue (63). Furthermore, a recent study in the fission yeast S. pombe , revealed that oxidation of the Pyp1 protein tyrosine phosphatase to slower migrating disulfide-bonded complexes, contributes to increases in Sty1 phosphorylation (48). Excitingly, we find that the C. albicans Ptp3 phosphatase is oxidised to slower migrating disulfide-bonded complexes following oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with work in other organisms showing that protein tyrosine kinases are susceptible to oxidative-stress mediated inhibition through oxidation of the active site cysteine residue (63). Furthermore, a recent study in the fission yeast S. pombe , revealed that oxidation of the Pyp1 protein tyrosine phosphatase to slower migrating disulfide-bonded complexes, contributes to increases in Sty1 phosphorylation (48). Excitingly, we find that the C. albicans Ptp3 phosphatase is oxidised to slower migrating disulfide-bonded complexes following oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the molecular mechanisms underlying kinase regulation by redox-active Cys residues is fundamental as it appears to be widespread in signaling proteins (Xiao et al 2020 ;Corcoran and Cotter 2013 ;Cao et al 2023 ) and provides new opportunities to develop specific covalent compounds for the targeted modulation of protein kinases (Weisner et al 2015 ). Moreover, redox-active Cys are major sensors of Reactive Oxygen Species (ROS), such as superoxide and peroxide, which function as endogenous secondary messengers to regulate various cellular processes (Schieber and Chandel 2014 ;Wani et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the molecular mechanisms underlying kinase regulation by redox-active Cys residues is fundamental as it appears to be widespread in signaling proteins (Xiao et al 2020 ;Corcoran and Cotter 2013 ;Cao et al 2023 ) and provides new opportunities to develop specific covalent compounds for the targeted modulation of protein kinases (Weisner et al 2015 ). Moreover, redox-active Cys are major sensors of Reactive Oxygen Species (ROS), such as superoxide and peroxide, which function as secondary messengers to regulate various cellular processes (Schieber and Chandel 2014 ; (Wani et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%